Effectiveness Of Fertilizer Distribution Policy For Farmers In Sumberbendo Village, Probolinggo District - Oktavia Putri Khoirril; Noftarida Dina Novita; Nova Dwi Nur Kumala Sari; Muhammad Akbar Putra Handoyo; Singgih Manggalou (Journal of Governance and Administrative Reform, 2023)
Abstract